On the thermal performance of nanofluid over a cylinder within a confined channel: The splitter effect - S.A.R. Sahebi; D.D. Ganji; J. Alinezhad (Case Studies in Thermal Engineering, 2023)
Implementing splitters in microchannels enhances fluid distribution, and nanofluids offer a promising approach to improving heat transfer efficiency. This study uses a home-written Lattice Boltzmann code to numerically investigate the integration of splitters and nanofluids in a copper-water-filled channel with varying Reynolds numbers (Re= 10 to 80) and volume fractions (0≤φ≤0.2) including a splitter at different positions and inclination angles under heat flux boundary condition. Results reveal that heat transfer augmentation occurs with an increase in flow and nanofluid usage compared to conventional fluids. The maximum Nusselt number (Nu) is achieved at a vertical position for all splitter plate locations showing a rise to more than 40% by increasing the φ to 0.1. The estimated Nusselt numbers obtained by the two correlation methods agree well with simulation results with a coefficient of determination (R2>0.9). These findings can be coupled with optimization techniques to determine the optimal conditions of splitters, improving heat transfer efficiency for some practical applications such as micro-heat sinks in electronic-cooling devices.